Desenvolvimento profissional docente de professoras nos primeiros anos de exercício da docência - Santana, Marcela de Souza (2017)
This investigation was developed in Master’s Degree Program of Postgraduate Program of Universidade Federal de Mato Grosso. It has as a thematic the professional teacher training with focus in the professional socialization process in beginning phase of professors that work in the first stage of Ensino Fundamental, in a municipal school in Cuiabá-MT. The main objective of this investigation is to comprehend how the beginner professors have the experience in front of challenges on the socialization process. For the development of the discussions, we looked for theoretical and methodological basis on the perspectives of Clandinin and Connelly that use the Narrative Inquiry as an inquiry method, which aims the senses and meanings comprehension of the narrated experiences in the educational exercise. To comprehend the training aspects and professional development of professors, I used as a base some authors such as: Marcelo Garcia, Mizukami, Nóvoa. This research was made through field notes of the researcher and written and oral narratives of the participating teachers that work in the first stage of Educação Básica in Cuiabá Municipality. We consider that the socialization teaching process starts with the professional insertion, being extended until the fifth year of educational exercise. From the analysis of the field texts, I consider that the teaching initiation is a period in which emerge several questionings about being a professor; for that reason, the researched teachers had the partners’ help in relation to the educational chores. Even though, the professors that took part in the investigation are in the beginning phase of their professional career, we perceived some levels of different development during their working with teaching. This study aims to contribute with the deepening of the thematic related to the professional development of beginner teachers, who work in the first stage, through narratives and experiences that happened in the school context, so that they can be helpful in the redetermination of the training process of those teachers, as well as, in the education quality.